Effect of Firm Characteristic to Profitability in PT Indofood Cbp, Sukses Makmur Tbk and PT Mayora Indah Tbk - Wiwiek Mardawiyah Daryanto; Donna Kartiningsih; Eka Lestari (Sekolah Tinggi Manajemen IPMI, 2019)
This research is aims to examine, analyze, and find the empirical evidence of the influence of firm characteristic proxied by firm age, firm size, sales growth, liquidity, and leverage on profitability proxied by return on sales in PT Indofood CBP, Sukses Makmur Tbk, and PT Mayora Indah Tbk. The study using employed multiple regression as tool for the analysis. The results of this study show that firm age, liquidity, and leverage have significant effect on profitability. However, the firm size and sales growth has no effect on profitability.